KONSEP SUSTAINABLE DEVELOPMENT SEBAGAI BENTUK PERLINDUNGAN TERHADAP KORBAN TINDAK PIDANA LINGKUNGAN HIDUP - Widowaty, Yeni (Jurnal Media Hukum, 2012)
The application of the principles of sustainable development in all sectors and activities become the main requirements to be internalized into policies and regulations in order that future generations will not inherit damaged and polluted environment. This research aims to identify, examine, and analyze the importance of legal protection and construct the ideal legal protection for the victims of environmental crime which have a sustainable development quality in the future.Â  This is a normative legal research which uses legislation law, case law, comparative, and conceptual as the approaches. The result of the research shows that philosophically, environmental crime victims should be protected because according to the theory of the law of the welfare state that the country is responsible for citizenâ€™s welfare. Moreover, the preamble of the Indonesia 1945 Constitution 1945 (UUD 1945) also stated that the duty of the country is to protect the whole nation and give a general welfare. In the future, the ideal of environmental laws is to construct a sanction in the form of compensation for the victim and take on the environmental restoration by applying the principle of strict liability.Key words: Sustainable Development, Victims, Environmental Crime